2020
DOI: 10.1371/journal.pone.0239254
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice regarding COVID-19 outbreak in Bangladesh: An online-based cross-sectional study

Abstract: In Bangladesh, an array of measures have been adopted to control the rapid spread of the COVID-19 epidemic. Such general population control measures could significantly influence perception, knowledge, attitudes, and practices (KAP) towards COVID-19. Here, we assessed KAP towards COVID-19 immediately after the lock-down measures were implemented and during the rapid rise period of the outbreak. Online-based cross-sectional study conducted from March 29 to April 19, 2020, involving Bangladeshi residents aged 12… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

157
447
29
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 471 publications
(657 citation statements)
references
References 24 publications
157
447
29
24
Order By: Relevance
“…Study participants who have degree & above (AOR: 1.9, 95% CI: 0.20-5.2, P-valve=0.003, AOR: 1.7), taking training (95% CI: 0.72 -10.7, P-valve=0.004), being health professional (AOR: 4.5, 95% CI: 0.18 -7.7, P-valve=0.001) and from urban resident (AOR: 3.1, 95% CI: 0.88 -13.67, P-valve=0.001, respectively) were more chance to have positive attitude towards COVID-19 ( Table 5). The current study finding was in line with different studies done on the assessment of knowledge, attitude, and practice towards the pandemic in all KAPS findings [15][16][17][18][19][20] .…”
Section: Knowledge Attitude and Practice Of Study Participants Towasupporting
confidence: 92%
“…Study participants who have degree & above (AOR: 1.9, 95% CI: 0.20-5.2, P-valve=0.003, AOR: 1.7), taking training (95% CI: 0.72 -10.7, P-valve=0.004), being health professional (AOR: 4.5, 95% CI: 0.18 -7.7, P-valve=0.001) and from urban resident (AOR: 3.1, 95% CI: 0.88 -13.67, P-valve=0.001, respectively) were more chance to have positive attitude towards COVID-19 ( Table 5). The current study finding was in line with different studies done on the assessment of knowledge, attitude, and practice towards the pandemic in all KAPS findings [15][16][17][18][19][20] .…”
Section: Knowledge Attitude and Practice Of Study Participants Towasupporting
confidence: 92%
“…Nazli T et al reported that 48 percent adult population in India wore face mask (10). Whereas Ferdous MZ et al provided 98.7 percent statistics of mask adherence in Bangladesh (11). The difference in proportion re ection the number of cases presenting in each country daily.…”
Section: Discussionmentioning
confidence: 99%
“…The virus, first identified in Wuhan, China, in December 2019, has affected 215 countries, areas, or territories with 230,104 deaths and 3,272,202 positive cases globally, as of May 03, 2020 [2]. On March 11, 2020, the World Health Organization declared a pandemic [3], and the first three cases of COVID-19 were found in Dhaka, Bangladesh on March 08, 2020 [4][5][6]. Given the dense population of Bangladesh and other factors, COVID-19 has become a major public health concern in Bangladesh, as in other countries.…”
Section: Introductionmentioning
confidence: 99%